(untitled) (Innovative professional education, 2025)
The need to provide access to modern educational materials, adaptive methods, interactive learning, and optimization of educational processes in the professional training of future qualified workers in the machine-building industry has contributed to the active use of digital platforms. The article briefly describes the advantages and capabilities of this type of software product. The expected impact of integrating artificial intelligence technologies into digital platforms for the professional training of qualified workers in the machine-building industry on the development of science, society, economy, defense capability, technologies, environmental protection, health and quality of life, public policy, social sphere, education, and culture is described.